(untitled) (Palíndromo, 2018)
The conception of aesthetic experience in Discursive Semiotics will be approached from the reading of the statements that make up the last book produced by Algirdas Julien Greimas, “Da Imperfeição”, and its repercussions on the work of Eric Landowski., The positioning on aesthetic experience, assumed by the authors listed, points to the inseparability between the sensitive and intelligible dimensions in acts of reading and production of meanings of being in the world.